PENDIDIKAN ANAK BERWAWASAN KEWIRAUSAHAAN - Sinay, Francisca R (Magister Manajemen Universitas Wisnuwardhana, 2019)
Efforts to improve the quality of education in Indonesia have long been carried out. Improving the quality of education is one of the development priorities in the field of education. Seeing these conditions, the world of education must be able to play an active role in preparing educated human resources who are able to face the challenges of life both locally, regionally, nationally and internationally. It is not enough to master theories, but also be willing and able to apply them in social life. Not only able to apply knowledge in primary, secondary and tertiary education, but also able to solve various problems encountered in everyday life. Entrepreneurial education is education that applies principles and methodologies towards the formation of life skills for students through an integrated curriculum developed in schools. This paper tries to offer an entrepreneurial insight education model for pre-school level and primary school. With this model, if it is implemented, it is expected that the world of education will contribute significantly to improving the quality of human resources in Indonesia. The framework of entrepreneurship development among educators is felt to be very important. Because educators are 'agents of change' who are expected to be able to instill the characteristics, nature and character as well as the spirit of entrepreneurship or the soul of 'entrepreneur' for their students. Besides that the spirit of 'entrepreneur' is also very necessary for an educator, because through this soul, educators will have a work orientation that is more efficient, creative, innovative, productive and independent. Keywords: Children's Education, Entrepreneurship.